AZATAX: Acetazolamide safety and efficacy in cerebellar syndrome in PMM2 congenital disorder of glycosylation (PMM2‐CDG). Issue 5 (22nd March 2019) - Martínez‐Monseny, Antonio F.; Bolasell, Mercè; Callejón‐Póo, Laura; Cuadras, Daniel; Freniche, Verónica; Itzep, Débora C.; Gassiot, Susanna; Arango, Pedro; Casas‐Alba, Didac; de la Morena, Eugenia; Corral, Javier; Montero, Raquel; et al.
Abstract : Objective: Phosphomannomutase deficiency (PMM2 congenital disorder of glycosylation [PMM2‐CDG]) causes cerebellar syndrome and strokelike episodes (SLEs). SLEs are also described in patients with gain‐of‐function mutations in the CaV2.1 channel, for which acetazolamide therapy is suggested. Impairment in N‐glycosylation of CaV2.1 promotes gain‐of‐function effects and may participate in cerebellar syndrome in PMM2‐CDG. AZATAX was designed to establish whether acetazolamide is safe and improves cerebellar syndrome in PMM2‐CDG. Methods: A clinical trial included PMM2‐CDG patients, with a 6‐month first‐phase single acetazolamide therapy group, followed by a randomized 5‐week withdrawal phase. Safety was assessed. The primary outcome measure was improvement in the International Cooperative Ataxia Rating Scale (ICARS). Other measures were the Nijmegen Pediatric CDG Rating Scale (NPCRS), a syllable repetition test (PATA test), and cognitive scores. Results: Twenty‐four patients (mean age = 12.3 ± 4.5 years) were included, showing no serious adverse events. Thirteen patients required dose adjustment due to low bicarbonate or asthenia. There were improvements on ICARS (34.9 ± 23.2 vs 40.7 ± 24.8, effect size = 1.48, 95% confidence interval [CI] = 4.0–7.6, p < 0.001), detected at 6 weeks in 18 patients among the 20 responders, on NPCRS (95% CI = 0.3–1.6, p = 0.013) and on the PATA test (95% CI = 0.5–3.0, p = 0.006). Acetazolamide improved prothrombin time, factor X, and antithrombin. Clinical severity, epilepsy, and lipodystrophy predicted greater response. The randomized withdrawal phase showed ICARS worsening in the withdrawal group (effect size = 1.46, 95% CI = 2.65–7.52, p = 0.001). Interpretation: AZATAX is the first clinical trial of PMM2‐CDG. Acetazolamide is well tolerated and effective for motor cerebellar syndrome. Its ability to prevent SLEs and its long‐term effects on kidney function should be addressed in future studies. Ann Neurol 2019;85:740–751